Toward Personalized Oral Diagnosis: Distinct Microbiome Clusters in Periodontitis Biofilms - Wirth, Roland; Pap, Bernadett; Maróti, Gergely; Vályi, Péter; Komlósi, Laura; Barta, Nikolett; Strang, Orsolya; Minárovits, János; Kovács, Kornél L. (Frontiers in Cellular and Infection Microbiology, 2021)
Periodontitis is caused by pathogenic subgingival microbial biofilm development and dysbiotic interactions between host and hosted microbes. A thorough characterization of the subgingival biofilms by deep amplicon sequencing of 121 individual periodontitis pockets of nine patients and whole metagenomic analysis of the saliva microbial community of the same subjects were carried out. Two biofilm sampling methods yielded similar microbial compositions. Taxonomic mapping of all biofilms revealed three distinct microbial clusters. Two clinical diagnostic parameters, probing pocket depth (PPD) and clinical attachment level (CAL), correlated with the cluster mapping. The dysbiotic microbiomes were less diverse than the apparently healthy ones of the same subjects. The most abundant periodontal pathogens were also present in the saliva, although in different representations. The single abundant species Tannerella forsythia was found in the diseased pockets in about 16–17-fold in excess relative to the clinically healthy sulcus, making it suitable as an indicator of periodontitis biofilms. The discrete microbial communities indicate strong selection by the host immune system and allow the design of targeted antibiotic treatment selective against the main periodontal pathogen(s) in the individual patients.